KARAKTERISTIK PRODUK BAKERY DARI SHORTENING CAMPURAN TERNER MINYAK IKAN NILA, PALM STEARIN, DAN MINYAK SAWIT MERAH HASIL INTERESTERIFIKASI KIMIAWI - Sumartini Sumartini; Ayu Rizki Amalia (Pro Food, 2022)
Shortening is a product made from a mixture of saturated and unsaturated fatty acids that play a role in softening and softening the texture of bakery products. Applications using shortening in bakery products can be seen in the manufacture of steamed cakes, baked cakes, and donuts. The author's purpose of conducting this study was to determine the effect of shortening formulations and processing methods on the characteristics of the resulting bakery products. The experimental design was a completely randomized design (CRD) using five ternary fat mixtures with different ratios and methods, each Palm Stearin/Fish Oil/Red Palm Oil (PS/FO/MSM): F1 (95/2.5/2 .5), F2 (90/5/5), F3 (85/7.5/7.5), F4 (80/10/10) and F5 (75/12.5/12.5) and K (commercial shortening) and (%bb) were applied to 3 different processing methods. The total number of treatments was 18 treatments. The results of data analysis were tested using SPSS Version 22 with One way ANOVA and the test level was 5%. The test parameters on bakery products are water content, fat content, free fatty acids, PV, swellability, carotene and hardness. Based on the results of the study that the formulation of the resulting shortening ratio and the method of making bakery products affect the physical and nutritional characteristics of the resulting bakery products. Where based on physicochemical characteristics, the best treatment was obtained by using shortening with the code F3 (PS/MSM/FO = 85/7.5/7.5) because it showed that bakery product yields were better than other treatment codes and were closest to the characteristics of commercial shortening. is on the market.